2012
DOI: 10.1002/cphc.201100800
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms for Nanoparticle Formation between pDNA and siRNA Using Polyrotaxane as the Polycation

Abstract: Ratios that matter: Investigations of nanoparticle formation using polyrotaxane as a polycation reveal that the formations of pDNA and siRNA nanoparticles with polycations are dependent on the nitrogen/phosphate ratio and the molar ratio, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…[23,24]. We previously confirmed that pDNA particles condensed with DMAE-SS-PRX efficiently released DNA and showed a high transfection activity, when the positive particles were formed at a nitrogen/phosphate (N/P) ratio of 5 [11]. In this study, we prepared condensed pDNA nanoparticles at an N/P ratio of 5, and their diameters and ζ potentials were measured (Table 2).…”
Section: Evaluation For Efficiency Of Dna Release From Condensed Pdnamentioning
confidence: 58%
See 4 more Smart Citations
“…[23,24]. We previously confirmed that pDNA particles condensed with DMAE-SS-PRX efficiently released DNA and showed a high transfection activity, when the positive particles were formed at a nitrogen/phosphate (N/P) ratio of 5 [11]. In this study, we prepared condensed pDNA nanoparticles at an N/P ratio of 5, and their diameters and ζ potentials were measured (Table 2).…”
Section: Evaluation For Efficiency Of Dna Release From Condensed Pdnamentioning
confidence: 58%
“…Figure 3 shows the relationship between efficiency of DNA release (x-axis) and transfection activity (y-axis). Based on previous report that there would be a positive correlation between the efficiency of DNA release and transfection activity [11], it was expected that DMAE-SS-PRX with a high efficiency for DNA release would result in the production of a strong gene expression. The results in Figure 3 showed that the transfection activity was proportional to the efficiency of the DNA release to some extent.…”
Section: Evaluation For Transfection Activity Of R8-mendmentioning
confidence: 99%
See 3 more Smart Citations